The Theoretical Problems of Civil Religion and Political Religion: A Comparative Analysis of the Concepts of Civil Religion by J.J.Rousseau, E.Durkheim and R.Bellah - Ganbarov, Asaf (Scholarya Demo Journal of Ruby, 2024)
In this article, the concept of civil religion, a significant issue in social sciences, is comparatively examined in the context of the theories of J. J. Rousseau, E. Durkheim, and R. Bellah. To summarize, the concept of civil religion, defined as the sacralization of the state and nation, was first introduced by Rousseau, but subsequent research by Durkheim and Bellah transformed it into a relevant issue. This article compares J. J. Rousseau’s political religion approach with E. Durkheim’s concept of cultural and social civil religion. Furthermore, the theoretical problems associated with the concepts of civil religion and political religion are analyzed in modern sociological literature. The author argues that despite some researchers using the terms civil religion and political religion interchangeably, most scholars employ civil religion to refer to a set of values, beliefs and ceremonies that are formed by society itself. In contrast, political religion is primarily used to describe a set of beliefs imposed by totalitarian regimes, suppressing all beliefs and ideas other than the ruling ideology and considering them as rivals.Additionally, the article briefly reviews the opinions of researchers who criticize the theory of civil religion. Concerning the formation of civil religion in Azerbaijan, the author notes that, as in modern nation-states, various elements of civil religion are observed in Azerbaijan. For instance, respect for the national flag and national anthem, the concept of homeland, and instilling values such as martyrdom can be cited as examples. However, the author believes that associating these ideas and ceremonies with traditional religions, particularly Islam, suggests that independent civil religion in Azerbaijan is still in its early stages of development and it is not yet possible to speak of a complete and independent civil religion.